Monografía en la temática de apalancamiento financiero y operativo (2013)
The present work aims the recopilation of the necessary information for the construction of a theoretical framework in the topic of financial and operative leverage in the organizations. This document is based mainly on stablishing a temathic order, of the esencial content all the necessary elements for the understanding of one of the financing tools, that are named financial and operative leverage, starting from the general to the particular, that is to say, is made a tour of finance and its evolution, identify and explain each one of the components that are involved in the conformation of the financial and operative structure of the organizations, taking the elements of each one of the financial decisions (investment, finanacing and dividends). In conclusion the finality of this monograph is centered on serving the student community of La Universidad de el Quindío, as a reference of query that contains a clear, concise and practical both theoretical and procedure of the aplication of this technique of high rentability in the companies.